Optimalisasi Peran partisipasi Masyarakat dalam mewujudkan Desa Mojosarirejo bebas Narkoba - Mohamad Sholahuddin; Putut Hadi Suprayitno; Lily Solichul Mukminah; Lambang Siswandi; Moh. Kamaluddin; Novellita Sicillia Anggraini (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2025)
Community Service Activities were carried out in Mojosarirejo Village, Kemlagi District, Mojokerto Regency with the target of providing an understanding of Optimizing the Role of Community Participation in making Mojosarirejo Village Drug Free. Implementation of community service in Mojosarirejo Village with the main aim of providing education and literacy to the community about the dangers of drugs, as well as their bad effects on the human body, as well as criminal charges against users and dealers. This theme was chosen because drug trafficking in Mojosarirejo Village is very worrying. The circulation is massive and organized so that many village teenagers become drug users. The increasing distribution and use of drugs also has an impact on increasing crime rates. Preventive efforts in the form of early prevention need to be strengthened by involving the active participation of village communities, so that the space for drug trafficking can be narrowed. With the knowledge gained, the public can recognize and take preventive steps. Saving the younger generation from the influence of drugs is a form of effort to protect the nation's generation. The socialization carried out in Mojosarirejo Village, Kemlagi District, Mojokerto Regency, involved all elements of Village institutions, Youth Elements, Religious Leaders to work together and unite to eradicate drug trafficking.